PROJECTING OF THE INDIVIDUAL WORK OF STUDENTS STUDYING INFORMATICS - Mikhail I. Umansky (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the paper the peculiarities of the individual project work on informatics of the first-year students of the specialty 08 are considered. The important feature of informatics as a subject depends upon the wide distribution of means and technologies of informatics in all the spheres of the activity of people of all ages, that causes certain problems in the systematic study of the professional methods of work. The majority of graduates have no skills of planning and organization of individual work. The paper offers to narrow the university requirements on the basis of traditional university methods usage, and motivation and encouraging of individual planning and self-control. The attention is paid mainly to the laboratory work aimed at the formation of procedural knowledge. As means of self-control for the laboratory practice tasks we offer to use maps of self-control and control. Such maps contain the detailed description of skills and knowledge that should be learned by the student in order to get the planned competences. To plan the individual work at laboratory practice we offer to use the learning technological maps designed by students on the basis of patterns. On the basis of dialogue and group discussions the subject-subject relations are formed that encourage responsible attitude to the given task. Efficient combination of the usage of patterns as the results of practical work and creative search for the best algorithms and procedures allows to move to the formation of cultural and professional competences in the course of informatics step by step.